Reconstruction of the Healthcare Service Dispute Resolution System Through the Establishment of a Special Hospital Court - Arie Setyo Wahyudi; Aris Nur Ramdhani; Amrollah Latupono; Danissa Alma Rosela; Bahtiar Husein; Ahmad Jaeni (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The increasing number of healthcare disputes in Indonesia demonstrates the need for a more effective, equitable, and legal resolution mechanism that provides legal certainty for all parties. In practice, healthcare dispute resolution often involves various institutions, such as the Indonesian Medical Disciplinary Honorary Council (MKDKI), the police, and the courts. However, differences in assessments and decisions between these institutions often lead to legal disharmony, where a medical procedure may be declared not to violate professional discipline by the MKDKI, but still result in criminal proceedings or a different civil verdict in court. This situation has the potential to create legal uncertainty for hospitals, medical personnel, and patients, disrupting the provision of healthcare services. This study aims to analyze the weaknesses of the current healthcare dispute resolution system and formulate a concept for the establishment of a Special Hospital Court as an effort to reconstruct the healthcare legal system in Indonesia. The study uses a normative juridical method with a statutory regulatory and conceptual approach, as well as case studies of decisions that demonstrate differences in assessments between professional disciplinary bodies, law enforcement officials, and the courts. Data are analyzed qualitatively to identify the ideal legal framework for resolving healthcare disputes. The research findings indicate that the healthcare dispute resolution system remains fragmented and unintegrated, potentially resulting in contradictory decisions. Therefore, reconstruction is needed through the establishment of a Special Hospital Court with specialized competence in the healthcare sector, involving judges who understand medical and legal aspects of healthcare, and utilizing the results of professional disciplinary examinations as a primary consideration in the judicial process. The presence of this special court is expected to achieve legal certainty, substantive justice, and balanced legal protection for patients, medical personnel, and hospitals in resolving healthcare disputes.